An Eulerian-Lagrangian method for wet biomass carbonization in rotary kiln reactors. (April 2021) - Tavakkol, Salar; Zirwes, Thorsten; Denev, Jordan A.; Jamshidi, Farshid; Weber, Niklas; Bockhorn, Henning; Trimis, Dimosthenis
Abstract: This study presents numerical simulations of rotary kiln reactors for wet biomass carbonization. For this, a numerical tool has been developed resolving the carbonization process in time and space. Biomass particles are represented by Lagrangian particles that collide and form a moving bed. The gas phase is treated as an Eulerian phase. Both phases are fully coupled with the exchange of momentum, energy, and mass of chemical species. The tool is implemented in the open-source OpenFOAM® framework and additional submodels for devolatilization, drying and radiation have been developed for the conditions relevant during the carbonization process. In this way, models for the complex physical processes are combined in a single simulation tool. A rotary kiln reactor of laboratory-scale is used to validate the numerical tool and to perform parameter studies to determine biomass conversion in dependence on the wall temperatures. The results also give insight into the sensitivity of biomass to carbon conversion with respect to the biomass moisture content and mass flow rate. The validated tool is used to perform simulations of an industrial-scale rotary kiln reactor, which are carried out on a supercomputer on up to 1120 CPU cores. The simulations demonstrate the effect of different wall temperatures on the optimal conversion of biomass to char and help to choose the optimal wall temperatures depending on the biomass properties. Highlights: A numerical solver that combines required physical submodels to simulate wet biomass carbonization in industrial reactors. Full time and space resolved simulation of thermal conversion of wet moving bulk in a large-scale rotary kiln reactor. Validation of simulation results with laboratory-scale experiments. Optimization of the numerical solver for industrial-scale and long-time simulations on parallel supercomputers. Parameter studies for the industrial-scale rotary reactor to investigate conversion sensitivity and product quality.